Effect of Solution Treatment on Thermal Conductivity of Porous NiTi Shape Memory Alloy - Kaya, Mehmet; Bugutekin, Abdulcelil; Orhan, Nuri (Springer/Plenum Publishers, 2011)
In this study, a new solution treatment solution treatment under loading was applied to a porous Ni-50 at.%Ti shape memory alloy (SMA), which was fabricated by self-propagating high-temperature synthesis (SHS), to explore the microstructural improvement regarding single-phase NiTi. The effects of solution treatment under loading and without loading on the phase constituent and thermal conductivity were investigated and discussed. The phase constituent and thermal conductivity of the specimens considerably changed with solution treatment under loading, but they were not affected significantly with solution treatment without loading. Intermetallic phases such as B19'(NiTi), Ti2Ni, and Ni4Ti3 disappeared, the density of the B2(NiTi) phase increased with solution treatment under loading, and thus the thermal conductivity was increased. It was also seen that the thermal conductivity of porous NiTi was less than that of solid NiTi.
Keywords: Fourier Law; Porous NiTi; Solution treatment under loading; Thermal conductivity